2021
DOI: 10.1186/s12967-021-02983-3
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-7 deficiency promotes stemness properties in colorectal cancer through Sox9-mediated Wnt/β-catenin signalling

Abstract: Background Colorectal cancer (CRC) is a common malignant tumour of the digestive tract that is characterized by high patient morbidity and mortality rates. Claudin-7 (Cldn7), a tight junction protein, was recently reported to function as a candidate tumour suppressor gene in CRC. Our previous study demonstrated that the large intestine of C57/BL6 mice showed intestinal adenomas and abnormal Ki67 expression and distribution in the intestinal crypt when Cldn7 was knocked out. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…27 The Claudin-7 knockdown modulates the Sox9mediated Wnt/β-catenin pathway to enhance stemness properties in CRC. 28 RNF6 stimulates the Wnt pathway to strengthen radio resistance in CRC. 29 In addition, FUBP1 affects the Wnt/β-catenin cascade to accelerate stemness and metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The Claudin-7 knockdown modulates the Sox9mediated Wnt/β-catenin pathway to enhance stemness properties in CRC. 28 RNF6 stimulates the Wnt pathway to strengthen radio resistance in CRC. 29 In addition, FUBP1 affects the Wnt/β-catenin cascade to accelerate stemness and metastasis in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, KCTD9 reduces β‐catenin levels to retard the Wnt/β‐catenin pathway in CRC 27 . The Claudin‐7 knockdown modulates the Sox9‐mediated Wnt/β‐catenin pathway to enhance stemness properties in CRC 28 . RNF6 stimulates the Wnt pathway to strengthen radio resistance in CRC 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our results Philip et al, Bhat et al and Wang et al concluded that Claudin-7 low expression or downregulation induced EMT, which plays a major role in CRC invasion, progression and metastasis process [ 30 , 31 , 32 ]. Furthermore, Xu et al analyzed the effects of Claudin-7 knockdown in CRC stem cells through cell proliferation assay, migration assay, apoptosis assay and reported changes in cell characteristics such as promotion of cell proliferation, migration, and inhibition of cell apoptosis and the presence of EMT [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR was performed as previously described [ 14 ]. TRIzol (Thermo Fisher Scientific) was used to extract cellular RNA, after which an All-in-One First-Strand cDNA Synthesis Kit (GeneCopoeia, Rockville, MD, USA) was used to prepare cDNA.…”
Section: Methodsmentioning
confidence: 99%